Synthesis and investigation of thermal properties of octakis (ethylsulfanyl) porphyrazine - Aytan Kilicarslan, Fatma; Elmali, Fikriye Tuncel; Manav Yalcin, Sabiha (YILDIZ TECHNICAL UNIV, 2022)
Between tetrapyrrole macrocycles, porphyrazines show both special physical and chemical properties as metal free and transition metal complexes. Many new studies have demonstrated effective coordination chemistry, great chemical, thermal, and photochemical stability, as well as technological applications to this macrocycle. In the work, it has been planned to synthesize asymmetric porphyrazine having seven ethylsulfanyl groups and one bromine by using a different method. In this way, asymmetric(ethylsulfanyl) porphyrazines were synthesized by replacing one ethylsulfanyl-alkyl chain on macrocycle with a hydrojen atom. The bromination of this product has resulted monobromoporphyrazine derivative. Thermal analysis of the compounds were done by differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA) (between 50-1200 degrees C). The structures of these compounds were characterized by using UV, FT-IR, MS, 1H NMR, elementel analysis.
Keywords: Porphyrazines; Thermal Analysis; TGA; Ethylsulfany; DISCOTIC MESOMORPHISM; COMPLEXES; PHTHALOCYANINES; SUBSTITUTION; AGGREGATION; SPECTRA; Engineering